Some shallow-water hydroids (Cnidaria: Hydrozoa) from the central east coast of Florida, USA - Calder, Dale R. (Zootaxa, 2013)
This paper gives a systematic account of 67 species, referable to 22 families and 40 genera, identified in a small collection of hydroids from the central Atlantic coast of Florida between Melbourne and Palm Beach. The fauna mostly comprises an assemblage of tropical western Atlantic species ranging northwards along the southeastern coast of the United States. One new species, Lafoea intorta, is described. Applying Reversal of Precedence provisions in zoological nomenclature, the widely-used generic name Halopteris Allman, 1877 is designated as valid and as a nomen protectum, while its virtually unused senior synonym Halicornaria Hincks, 1865 (not Halicornaria Allman, 1874) is reduced to a nomen oblitum. The genus Pasya Stechow, 1922 is resurrected for the hydroid generally known as Dynamena quadridentata (Ellis & Solander, 1786). Laomedea tottoni Leloup, 1935 is shown to be a junior objective synonym of Clytia fragilis Congdon, 1907, which in turn is a junior subjective synonym of Clytia linearis (Thornely, 1900). Obelia oxydentata Stechow, 1914 is recognized as distinct from O. bidentata Clark, 1875. Hincksella brevitheca Galea, 2009, first described from Cuba, is reported for only the second time; records of the species are added here from Grand Cayman Island and the Caribbean coast of Panama as well as from the Atlantic coast of Florida. Also reported for the second time is Antennella incerta Galea, 2010, previ-ously known only from Guadeloupe in the Caribbean Sea. The true Halopteris diaphana (Heller, 1868), known from the Mediterranean Sea and from Brazil, is reported for the first time from the western North Atlantic. Earlier records of the species in the region are based on misidentifications of H. alternata (Nutting, 1900). Male gonothecae of Halecium calderi Galea, 2010 are reported and illustrated for the first time.